Erratum to: Atomic mobility in titanium grade 5 (Ti6Al4V) - Editorial (Journal of Mining and Metallurgy. Section B: Metallurgy)
This erratum concerns a correction in the author name and affiliation of the original article [1] on page 65 and 77. Link to the corrected article 10.2298/JMMB180620030G